Information literacy and the ethics of academic writing - Sanches, Tatiana (2017)
This article proposes to conduct a thorough reflection on the concept of ethics of academic writing in higher education, under the conceptual framework of information literacy. To support this reflection on this ethical component, we carry out a review of the literature and previously reported experiential practices regarding the use of documentation and information analysis, particularly those held in school libraries. Recognizing the need for information from the outset of their academic written work, students are proposed to develop a set of research practices and use information ethically.